PRODUCT DEVELOPMENT OF MOTORCYCLES EMERGENCY WHEELS EQUIPMENT USING THE DESIGN FOR ASSEMBLY (DFA) METHOD - Moh. Miladun Hakimin Alim; Mr Rusindiyanto (Journal of Industrial Engineering Management, 2023)
Motorcycles are a popular mode of transportation that people widely use to facilitate their daily activities. Behind the advantage, motorcycles also have disadvantages. As we often encounter or even experience ourselves, namely tire leaks. Riding a motorcycle with a punctured tire can exacerbate and endanger the user. Thus, the motorcycle must be pushed manually to the workshop for repairs which will undoubtedly require a lot of time and effort. Moreover, motorcycle users will feel tired and uncomfortable. From these issues, a solution was devised as a motorcycle emergency wheel tool. This tool's function is to support the leaking part of the motorcycle wheel and is inserted into the device that has been made so that the leaking tire is not damaged. The method used is designed for assembly (DFA). This method aims to study the processes and products of competitors in terms of design, quality, selection of materials, components, and production processes and then evaluate the assembly of manufactured products to design superior products. Based on the results of the development of a motorcycle emergency wheel tool that has been carried out, the innovative product is proven to have a lower price with a difference of Rp. 22,000 from the earliest product price. The assembly efficiency, earlier worth 0.9062 or 90.62%, can be reduced to 0.8169 or 81.69% by implementing innovative product designs.